Cork Oak Trees (Quercus suber L.). - Alvarez, Rubén; Toribio, Mariano; Cortizo, Millán; Ordás Fernández, Ricardo-Javier (Methods in molecular biology (Clifton, N.J.), 2006)
A transformation system for selected mature Quercus suber L. trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses are inoculated with AGL1 strain harbouring the plasmid pBINUbiGUSint, which carries the nptII and uidA genes. Evidence of stable transgene integration is obtained by polymerase chain reaction for nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos are germinated and successfully transferred to soil.
The following values have no corresponding Zotero field: periodical: Methods in molecular biology (Clifton, N.J.) accession-num: 17033056 electronic-resource-num: 10.1385/1-59745-131-2:113
Keywords: AGL1; Agrobacterium tumefaciens; Cork oak; Fagaceae; kanamycin resistance; pBINUbiGUSint; Quercus suber; Somatic embryogenesis; Tree genetic transformation; β-glucuronidase